PENGARUH PENGENDALIAN INTERN TERHADAP EFEKTIVITAS PENJUALAN PADA PT.HARJA SUKSES MAKMUR - Ema, Yenna Anggra (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2014)
The purpose of this research is to find out the influence of internal controls which consist of environmental control, risk assessment, communication and information, control activity and supervision either simultaneously or partially to the sales activities. The result of examination shows that the influence of internal controls which consist of environmental control, risk assessment, communication and information, control activity and supervision to the sales activity is significant. This result is strengthened by the acquisition of correlation coefficient of 88.1% which shows correlation or relation among these variables simultaneously to the PT Harja Sukses Makmur Surabaya sales effectiveness has strong relation. The results of examination show that each internal control variable has positive and significant influence to the PT Harja Sukses Makmur Surabaya sales effectiveness. This condition is shown by the significant levels of each variable is below Î± = 5%.Keywords: Internal Control, Sales Effectiveness, Determination Coefficient